2014
DOI: 10.1007/978-3-642-38436-3
|View full text |Cite
|
Sign up to set email alerts
|

Error Correction in the Foreign Language Classroom

Abstract: The series brings together volumes dealing with different aspects of learning and teaching second and foreign languages. The titles included are both monographs and edited collections focusing on a variety of topics ranging from the processes underlying second language acquisition, through various aspects of language learning in instructed and non-instructed settings, to different facets of the teaching process, including syllabus choice, materials design, classroom practices and evaluation. The publications r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0
20

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 263 publications
(700 reference statements)
0
59
0
20
Order By: Relevance
“…At the same time, successful development of speaking skills poses a major challenge, particularly in situations in which learners have scant access to the target language (TL) outside the classroom (Majer, 2003;Ortega, 2007;Pawlak, 2004Pawlak, , 2006Pawlak, , 2014, which, despite all the technological advances, is still the case in most foreign language contexts. The difficulty involved in developing speaking skills in the TL has been stressed by many specialists in the area of second language acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, successful development of speaking skills poses a major challenge, particularly in situations in which learners have scant access to the target language (TL) outside the classroom (Majer, 2003;Ortega, 2007;Pawlak, 2004Pawlak, , 2006Pawlak, , 2014, which, despite all the technological advances, is still the case in most foreign language contexts. The difficulty involved in developing speaking skills in the TL has been stressed by many specialists in the area of second language acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…These studies largely investigate focused correction or are limited to one linguistic feature (Pawlak 2014). However, analyses reveal a considerable variation of teacher-and learner-related, psycholinguistic as well as linguistic factors (Goldstein 2008), which means that feedback is a complex research issue.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that a highly controlled practice activity generally requires more error correction than one where the focus is oral fluency. By contrast, things were more complex in meaning-oriented contexts as there were many selections for repair by the teachers (Nassaji, 2015;Pawlak, 2014).…”
Section: Resultsmentioning
confidence: 99%